Language use and attitudes among Chinese adolescents in Miri, Sarawak / Hoon Swee Kim - Hoon, Swee Kim (2017)
Language use or choice is an issue in multiethnic and multilingual countries such as Malaysia. Most Malaysians can speak more than one language. They are able to choose a suitable language which is appropriate with the addressee, topic or location. This study aims to explore the languages used by Chinese adolescents in Miri, Sarawak in five selected domains: family, school, transactional, government department and social media. The study also aims to survey the attitudes of Chinese adolescents in Miri, Sarawak towards the usage of Mandarin, English, Malay as well as their own ethnic languages. In addition, this study aims to detect factors that affect the Chinese adolescents’ language use in Miri, Sarawak. Questionnaire, interview and observation methods were used in this study to obtain data. A total of 100 Chinese adolescents in a Chinese conforming school in Miri, Sarawak, were chosen as respondents. Some of these respondents were also interviewed. The findings showed that Chinese adolescents in Miri gave priority to Mandarin within the family, school, transactional and government department domains, but English in the social media domain. The attitudes towards the usage of Mandarin and English were positive, however, the attitudes towards the usage of Malay was negative. Although the respondents showed positive attitudes towards their own ethnic languages but contradictory to their language use. The respondents perceived and judged the English language as the highest and most positive compared to the other languages. Factors such as low Malay proficiency, lack of interest in learning Malay and lack of motivation lead respondents not to choose Malay as the language of priority in the selected domains. The findings indicated that the Chinese adolescents’ language attitudes were closely related to their personal backgrounds, the language use in social environments and their language abilities.